2023
DOI: 10.1021/acs.jafc.2c08170
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol and 3′-Hydroxypterostilbene Alleviate Inflammatory Bowel Disease by Maintaining Intestinal Epithelial Integrity and Regulating Gut Microbiota in Mice

Abstract: Inflammatory bowel disease has become a significant health concern across the globe, causing frequent and long-term harm to the digestive system. This study evaluated the effect of piceatannol (PIC) and 3′-hydroxypterostilbene (HPSB) on dextran sulfate sodium (DSS)-induced colitis in mice and investigated whether their effects are exerted through the amelioration of gut barrier dysfunction to reduce the severity of colitis. The findings showed that both PIC and HPSB attenuated inflammation by inhibiting the TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In addition, compared with the NC group, the spleen index of the MC group was significantly increased ( p < 0.01), while the treatment with DOP could reverse the spleen swelling caused by inflammatory infiltration. Histological evaluation also confirmed that DOP reduced the direct damage of colon and ileum by inflammation …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, compared with the NC group, the spleen index of the MC group was significantly increased ( p < 0.01), while the treatment with DOP could reverse the spleen swelling caused by inflammatory infiltration. Histological evaluation also confirmed that DOP reduced the direct damage of colon and ileum by inflammation …”
Section: Discussionmentioning
confidence: 56%
“…Histological evaluation also confirmed that DOP reduced the direct damage of colon and ileum by inflammation. 30 Apparently, DOP significantly inhibited the secretion of TNF-α, IL-1β, and IL-6 levels (p < 0.05), which are considered to be the major proinflammatory cytokines that aggravate the inflammatory response and cause colonic tissue damage. 31 The results of RT-qPCR confirmed the above results, although not to the level compared to the normal.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have also demonstrated that the Lactobacillus probiotic can potently alleviate intestinal inflammation in mice and positively correlate with TJ expression levels. 47 Moreover, Allobaculum i promotes tryptophan metabolism, which contributes to the relief of intestinal inflammation. 48 However, it should be noted that some Bacteroides can damage the mucous membrane layers, which may aggravate colitis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The gut microbiota analysis followed a previously described methodology . Genomic DNA of gut bacteria was isolated and purified using an InnuPREP Stool DNA kit following the manufacturer’s protocol, with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal permeability was assessed by measuring the amount of FITC-dextran in the bloodstream following oral administration, as previously described. , In brief, each mouse was administered 400 mg/kg of FITC-dextran (molecular weight, 4 kDa; Sigma-Aldrich) via gavage. A blood sample obtained 2 h later was initially centrifuged (10,000 g at 4 °C) for 10 min, and the serum was collected and placed into a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%